Desain sarana informasi di Taman Samarendah Samarinda - Andi Farid Hidayanto; Nur Husniah Thamrin (Institut Seni Indonesia Yogyakarta, 2021)
Samarendah Park is one of the new icons in Samarinda City. Its function has been felt by the people of Samarinda since it opened. This park can be used as a place to exercise, play children, or just relax. Now the park which is in the center of Samarinda City preening becomes increasingly beautiful. Taman Samarendah is reorganized so that it can be enjoyed more and more by Samarinda residents and tourists. Therefore, a signage is needed that is used to make information that guides the place and appeals. The purpose of this design is to make an information board that can provide information about Samarendah Park and facilities around the park. In this design process using the Vinod Ghoel method which includes Preliminary Design, Design Development, Final Design & Prototype. This design produces a product that is the Samarendah park information board. With the existence of the Samarendah park information board, it is hoped that it can facilitate access to information on places and appeals on location for visitors